EVALUATION OF THE DISTRIBUTION MODELS OF "BURITI" AND "PARATUDO", ARBOREAL SPECIES OF THE PANTANAL, WITH DATA OF THE CLIMATE OF THE QUATERNARY AND THE PRESENT - Sciamarelli, Alan; Torgeski, Mariele Ramona (UFPR, 2019)
During the Quaternary, climatic variations caused changes in the size of vegetation formations in the Pantanal, promoting the expansion of seasonal forests at the beginning of the Holocene. Climatic conditions change the patterns of vegetation diversity on continental scales. Mauritia flexuosa L. f., The "Buriti", is a palm tree that explores humid environments with acid soils. While, Tabebuia aurea (Silva Manso) Benth. &Hook.f. ex S.Moore is a species of monodominant occurrence in the Pantanal in extensive areas locally denominated as "paratudal". Data sets of past eras have contributed to the study of plant species biogeography. The models of the potential distribution of these species were generated from the algorithm of the Maxent program with climatic data set of the Last Glacial Maximum (ca 22,000 years AP), Holocene Medium (ca. 6,000 years AP) and present time in two different versions. Potential distribution models with climatic packets from the present in the newer version presented areas of environmental suitability greater than in the older version. In the Holocene Middle and Late Glacial Maximum periods, the areas of environmental suitability were higher than in the newer present version. Many studies on climatic variations on the South American continent confirm the suggestions of the proposed models. The areas of environmental suitability of the species treated in the present are smaller in comparison with Last Glacial Maximum and Average Holocene. The species presented a potential distribution according to the biogeographic history of South America.